Social and psychological aspects of the influence of stereotypes on the behaviour of consumers on the Russian market - Shumilova, Svetlana (2020)
The goal of this work is to explore the sociological and psychological problems of having stereotypes of behaviour on the Russian market in the study group, its cultural aspects, and the model consumer decision at the time of acquaintance with the goods.The theoretical part of this work will be based on sociological and psychological theories, marketing studies and concepts, cultural specifics, and influence of them to people. The methodology part is dealing with the research of Russian consumers of the study group.